Penerapan Diversi Anak Yang Berhadapan Dengan Hukum Dalam Mewujudkan Keadilan Restoratif - Machmud, Amir; Agus (Jurnal Justice Aswaja, 2023)
This study aims to determine and analyze the Diversion Mechanism for Children in Conflict with the Law for Narcotics Crimes and the urgency of implementing diversion for children in conflict with the law in realizing restorative justice. This type of research is normative legal research. Based on the research, it is concluded that the implementation of diversion for children who commit narcotics crimes based on Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, reviewed from the legal position of diversion for children who abuse narcotics in the perspective of criminal law development, is a non-penal policy step for handling children who commit juvenile crimes, because their handling is diverted from the juvenile justice system. Diversion is based on the assumption that the process of handling children through the juvenile justice system is more likely to be negative than positive for the development of children. In relation to the handling of children who abuse narcotics, the main problem arising from the juvenile criminal justice process or a criminal decision is the stigma attached to convicts of narcotics abuse after the completion of the criminal justice process. The increasing tendency for drug abuse by children encourages efforts to overcome and handle it specifically in the field of juvenile criminal law. Diversion with the Restorative Justice approach in its development is a settlement of child criminal cases that has been practiced by various countries, including in Indonesia which is regulated in Law No. 11 of 2012 concerning the Child Criminal Justice System and Government Regulation No. 65 of 2015. The concept of diversion regulated in the Criminal Justice System in Indonesia is to place an obligation to carry out Diversion in every stage of the judicial process (investigation, Prosecution and Trial).